Examining local institutional networks for sustainable disaster management: Empirical evidence from the South-West coastal areas in Bangladesh. Issue 124 (October 2021) - Mohibbullah, M.; Gain, Animesh K.; Ahsan, Md. Nasif
Highlights: Local social networks are a vital contributor to community resilience from disasters. Social network analysis was applied for local horizontal disaster management institutions in Bangladesh. The relationship among actors are strong during preparedness and response phases than recovery and mitigation. The collaboration and coordination need to be enhanced during recovery and mitigation phases. The actual implementation of the disaster management policies seems to be far behind what the policy documents indicate. Abstract: Local social networks are vital contributor to community resilience and recovery from disasters. We aim to assess how collaboration among local formal actors varies during different phases of disaster. We also identify the gaps in local institutional collaboration between policy and practice. The social network analysis is used to measure the network structure for coastal disaster management at the bottom level administrative (i.e., Union) in Bangladesh. We consider three disaster-prone locations in the southwest part of coastal Bangladesh. The following network matrices are used to quantify ties among the actors of the local disaster management committee: degree, betweenness, and eigenvector. The results reveal that the local committee members are highly active during the preparedness and the response phase. The network structure varies among studied locations due to multiple factors such as diverse leadership capacities of the actors, road network, and physical characteristics of the areas. Although Bangladesh is internationally acknowledged for disaster management activities, we find very poor collaboration among actors during the recovery and mitigation phase. The collaboration and coordination need to be enhanced during the recovery and mitigation phases for sustainable disaster management. The actual implementation of the disaster management policies is far behind what the policy documents indicate. Proper implementation of the roles and responsivities specified in the policy documents is therefore needed.